Good game : Christianity and the culture of sports - Hoffman, Shirl J., 1939- (Baylor University Press, 2010)
Good Game retells numerous fascinating stories from the world of ancient and contemporary sports and draws on the history of the Christian tradition to answer "What would it really mean to think Christianly about sport?" --from publisher description